Handbook of bone engineering - Abu Bakar @ Zakaria, Md Zuki; Kaveh, Kamran; Hussein, Bahaa Fakhri; Mohamed Mustapha, Noordin (Universiti Putra Malaysia Press, 2011)
Bone Tissue Engineering which is classically referred as the implantation of a scaffold seeded with appropriate population of seed cells and/or growth factor has recently been heralded as the strategy to generate new bone, given that it can provide adequate amount of new bone volume and satisfactory bone regeneration potential. By increasing the lifespan and aging of the society, bone threatening defects are being more apparent; also, managing these defects have become more challenging and are not possible with the old means of treatments. Hence, other treating protocol should be aimed, among which bone tissue engineering is the most recent strategy that scientists use to help such patients. This book aim to unfold different strategies of bone tissue engineering and scaffold preparation to be accustomed to the intelligentsia regarding the knowledge of this attractive field.